A narrative inquiry into counsellor trainees' experiences of working with trauma. Issue 4 (4th July 2021) - Dayal, Helena; Buck, George; Clandinin, D. Jean
ABSTRACT: Within the last 30 years, a narrative of risk emerged around the negative effects of trauma work on counsellors. This singular narrative has not allowed for an interrogation of a view of trauma work as risky practice. Questioning the dominance of this singular narrative framed this research puzzle. Using narrative inquiry, Author 1 inquired into the experiences of three counsellor trainees enrolled in a Canadian doctoral program. The research intention was to understand how their experiences, both within and outside, as well as before and after, their counselling programs, shaped their views of trauma work. Author 1 engaged in four one-on-one conversations with each participant. Four resonant narrative threads emerged across participants' experiences: (1) Different experiential ways of coming to understand trauma; (2) Using the trauma lens to reflect on our own lives; (3) Storying trauma into our personal and professional lives; and (4) Making sense of trauma and vicarious trauma in the silences. These threads drew attention to the importance of reflective practice in training and supervision, including implications for instruction on trauma and supporting counsellor trainees within counsellor education programs.